INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENGEMBANGKAN KARAKTER SISWA SEKOLAH DASAR - Maulidia Dwi Wahyu Hayati; Iqnatia Alfiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon of deviant behavior among Indonesian teenagers such as violence and bullying shows that character education is needed from an early age. This character education can be instilled through various subjects, one of which is Pancasila education whose values are the main foundation of the nation. This study aims to examine the implementation of character education integration in Pancasila education subjects and identify the obstacles faced at SDN Plabuhanrejo Lamongan. The results of the study show that in order to integrate character education in Pancasila education learning, teachers must prepare lesson plans that are in accordance with the syllabus and determine the characters instilled according to class level, then teach students using various media. In the process, teachers face several obstacles, such as the diversity of students' abilities in understanding the material and the influence of the external environment that cannot be controlled by the teacher. Therefore, an adaptive learning approach, family support, and synergy with the community are needed so that character education in Pancasila education subjects runs well and sustainably.